2023
DOI: 10.1002/tea.21869
|View full text |Cite
|
Sign up to set email alerts
|

Instructional practices in secondary science: How teachers achieve local and standards‐based success

Abstract: This article reports on analyses of the instructional practices of six middle‐ and high‐school science teachers in the United States who participated in a research‐practice partnership that aims to support reform science education goals at scale. All six teachers were well qualified, experienced, and locally successful—respected by students, parents, colleagues, and administrators—but they differed in their success in supporting students' three‐dimensional learning. Our goal is to understand how the teachers' … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 73 publications
(116 reference statements)
0
0
0
Order By: Relevance
“…Much of the work around sensemaking has focused on sensemaking as a process of learning science for students (Odden & Russ, 2019). For example, Covitt et al (2024) showed that teachers who engaged students in tasks that asked them to martial multiple pieces of evidence together to try to explain natural phenomena, which they called sensemaking, were more likely to show learning gains than those who focused on students engaging in procedural activities that illustrated science ideas.…”
Section: Theoretical Framework: Organizational Sensemakingmentioning
confidence: 99%
“…Much of the work around sensemaking has focused on sensemaking as a process of learning science for students (Odden & Russ, 2019). For example, Covitt et al (2024) showed that teachers who engaged students in tasks that asked them to martial multiple pieces of evidence together to try to explain natural phenomena, which they called sensemaking, were more likely to show learning gains than those who focused on students engaging in procedural activities that illustrated science ideas.…”
Section: Theoretical Framework: Organizational Sensemakingmentioning
confidence: 99%